Prayer, Pop and Politics: Researching Religious Youth in Migration Society - Mattes-Zippenfenig, Astrid; Novak, Christoph; Mattes-Zippenfenig, Astrid; Novak, Christoph; Limacher, Katharina; Tunger-Zanetti, Andreas; Martens, Silvia; Endres, Jürgen; Hyökki, Linda; Hafez, Farid; Evolvi, Giulia; Lohlker, Rüdiger; et al. (Religion and Transformation in Contemporary European Society., 2019)
What is it like to be young and religious in migration society? This volume presents research at the intersection of religion, age and race. The chapters’ foci range from methodological challenges to conceptual work and empirical case studies. The authors present research on various religious traditions including contributions on young Alevis, Hindus, Buddhists and Muslims, and apply an array of theoretical angles among them feminist, post- and de-colonial perspectives. Furthermore, the volume engages in the debate over novel conceptual frameworks attuned to investigate contemporary manifestations of youth religiosity, for example in digital spaces. The methodological chapters advocate for reflexivity in the context of empirical research on religion in migration society and promote a self-evaluative assessment of researchers’ positionalities.